Biomedical engineering indices for cardiac function and dysfunction during filling and ejection phases - Zhong, Liang (2008)
This dissertation investigates their dynamic interrelations under physiological and medical conditions, using biomechanical engineering models for (i) left ventricular diastolic and systolic indices, using clinical data (involving simultaneous recordings of aortic pressure, LV pressure, LV volume and electrocardiogram from patients from National Heart Center at Singapore) and (ii) the aortic blood pressure profile using auscultatory cuff diastolic and systolic pressures along with the blood flow rate from the LV into the aorta.